Role of therapeutic plasma exchange in severe thyrotoxicosis secondary to grave’s disease with several organ decompensation: a case report and review of literature - Rozi, Nur Raziana; Zakaria, Miza Hiryanti; Shahar, Mohammad Arif (2017)
We report a case of 45 year-old lady whom had received therapeutic plasma exchange for severe thyrotoxicosis with several organ decompensations due to the overwhelming autoimmunity. She presented with symptoms of breathlessness, lethargy and atrial fibrillation with rapid ventricular response. She had underlying, untreated Grave’s disease for several years. Her serum thyroxine levels were markedly elevated. Despite reduction in thyroid hormones levels after initial treatment with anti-thyroid drug and lugol’s iodine, her clinical condition deteriorated with hypotension, worsening respiratory distress, acute kidney injury and liver failure. We suspect that the overwhelming autoimmunity has led to the consequent organs decompensation. Therapeutic plasma exchange was initiated which resulted in improvement of the clinical and biochemical parameters and thus, potentially appears to have an effective role in a complicating, overwhelming autoimmunity of severe thyrotoxicosis secondary to Grave’s disease.